Comparative analysis of hemotoxic, myotoxic, and inflammatory profiles of Calloselasma rhodostoma and Trimeresurus insularis venoms in mice - Aphrodita, Adiva; Sentono, Diva N.; Yudha, Donan S.; Purwestri, Yekti A.; Nuringtyas, Tri R.; Raharjo, Slamet; Wahid, Isra; Rahmi, Sri N.; Wahyudi, Setyanto T.; Sofyantoro, Fajar (Narra J, 2025)
Snakebite envenomation remains a significant medical concern, particularly in tropical regions where venomous snakes such as Calloselasma rhodostoma and Trimeresurus insularis are prevalent. Both venoms are known for their potent hemotoxic, myotoxic, and inflammatory effects, yet their differential impacts on systemic physiological pathways remain unclear. The aim of this study was to characterize the hematological, myotoxic, and inflammatory effects of C. rhodostoma and T. insularis venoms in a murine model and to explore their influence on systemic factors such as insulin-like growth factor 1 (IGF-1), which is critical for muscle repair and inflammation regulation. Mice were exposed to varying doses (20–100 µg) of C. rhodostoma and T. insularis venoms. Hematological parameters, muscle degeneration, inflammatory cell infiltration, and plasma IGF-1 levels were assessed to evaluate the venoms' systemic and local effects. Our data indicated that C. rhodostoma venom induced significant changes in blood coagulation, muscle edema, and inflammatory infiltration, with pronounced effects even at lower doses. Conversely, T. insularis venom showed a dose-dependent suppression of IGF-1 levels, highlighting its unique systemic impact. Both venoms caused severe muscle damage, characterized by structural disintegration and increased leukocyte infiltration, with C. rhodostoma eliciting a stronger inflammatory response at lower doses.Snakebite envenomation remains a significant medical concern, particularly in tropical regions where venomous snakes such as Calloselasma rhodostoma and Trimeresurus insularis are prevalent. Both venoms are known for their potent hemotoxic, myotoxic, and inflammatory effects, yet their differential impacts on systemic physiological pathways remain unclear. The aim of this study was to characterize the hematological, myotoxic, and inflammatory effects of C. rhodostoma and T. insularis venoms in a murine model and to explore their influence on systemic factors such as insulin-like growth factor 1 (IGF-1), which is critical for muscle repair and inflammation regulation. Mice were exposed to varying doses (20–100 µg) of C. rhodostoma and T. insularis venoms. Hematological parameters, muscle degeneration, inflammatory cell infiltration, and plasma IGF-1 levels were assessed to evaluate the venoms' systemic and local effects. Our data indicated that C. rhodostoma venom induced significant changes in blood coagulation, muscle edema, and inflammatory infiltration, with pronounced effects even at lower doses. Conversely, T. insularis venom showed a dose-dependent suppression of IGF-1 levels, highlighting its unique systemic impact. Both venoms caused severe muscle damage, characterized by structural disintegration and increased leukocyte infiltration, with C. rhodostoma eliciting a stronger inflammatory response at lower doses.